Degree of conversion and hardness of two different systems of the vitrebond™ glass ionomer cement light cured with blue LED - Calixto, Luiz Rafael; Tonetto, Mateus Rodrigues; Pinto, Shelon Cristina Souza; Barros, Erico Damasceno; Borges, Alvaro Henrique; Lima, Fabrício Viana Pereira; Andrade, Marcelo Ferrarezi de [UNESP]; Bandéca, Matheus Coelho (Jaypee Brothers Medical Publishing, 2013)
This study investigated the physicochemical properties of the new formulation of the glass ionomer cements through hardness test and degree of conversion by infrared spectroscopy (FTIR). Forty specimens (n = 40) were made in a metallic mold (4 mm diameter × 2 mm thickness) with two resin-modified glass ionomer cements, Vitrebond™ and Vitrebond™ Plus (3M/ ESPE). Each specimen was light cured with blue LED with power density of 500 mW/cm2during 30 s. Immediately after light curing, 24h, 48h and 7 days the hardness and degree of conversion was determined. The Vickers hardness was performed by the MMT-3 microhardness tester using load of 50 gm force for 30 seconds. For degree of conversion, the specimens were pulverized, pressed with KBr and analyzed with FT-IR (Nexus 470). The statistical analysis of the data by ANOVA showed that the Vitrebond™ and Vitrebond™ Plus were no difference significant between the same storage times (p > 0.05). For degree of conversion, the Vitrebond™ and Vitrebond™ Plus were statistically different in all storage times after light curing. The Vitrebond™ showed higher values than Vitrebond™ Plus (p < 0.05). The performance of Vitrebond™ had greater results for degree of conversion than Vitrebond™ Plus. The correlation between hardness and degree of conversion was no evidence in this study.
Keywords: Degree of conversion; Glass ionomer cement; Hardness.